Ilocutionary speect act used in advertisement in Radio Damai FM Pariaman - Annisa Ainur Rahman; Herlin Triana; Rohaidah Binti Haron; Vivi Indriyani (Universitas Asahan, 2024)
Very significant technological developments do not hamper the existence of radio as one of the broadcast communication media. Various advertisements still trust radio as a distributor of information that has the potential to influence the public to promote a product. One of his efforts is to design unique and interesting communication. For this reason, this study examines the use of illocutionary speech acts in advertisements on Radio Damai FM Pariaman. There are various forms of speech acts in communication designed by the advertisements delivered. The method in this study is a qualitative-descriptive method. Based on the results of the study, it was found that the form of speech acts was 18.4%, 2) Directive as much as 39.5%, 3) Commissive as much as 15.8%, 4) Expressive 26.3%. The dominant speech act is a directive speech act because advertising in conveying information is more persuasive. It can be concluded that the speech acts used by advertisements on the radio in informing something not only about creating interesting language to influence radio listeners but can also have implications for learning in schools related to advertising text lessons and language skills.